Marriage and Divorce in Islamic Law: Sociological Implications for Modern Muslim Societies - Ismail, Muhamad; Faisal, Robitho Alam Hadi; Zainur, Zainur (Journal of Islamic Law El Madani, 2024)
This study examines the sociological implications of marriage and divorce in Islamic law in modern Muslim societies. It aims to explore how Islamic legal principles related to marriage and divorce are interpreted and applied in contemporary contexts and their impact on family dynamics, gender roles, and societal norms. The research employs a qualitative approach, with the data collected through interviews, focus groups, and ethnographic observation analyzed using thematic coding and narrative analysis. This approach allowed for identifying recurring themes and patterns and exploring participants' perceptions, attitudes, and personal stories. A combination of a literature review with a comprehensive review of existing scholarly works, legal texts, and sociological studies on Islamic marriage and divorce laws was conducted. This review helped to identify key themes, gaps in research, and the evolving nature of Islamic family law across different cultural and regional contexts. Sources include classical and contemporary Islamic jurisprudence (fiqh), academic articles, books, and NGO reports on women's rights and legal reforms in Muslim-majority countries. For the literature review, the study focused on sources published between 2000 and 2020. The following criteria guided the selection of literature to ensure that the materials were relevant, credible, and up-to-date with contemporary debates and issues: Relevance to Topic, Academic and Peer-Reviewed Sources, Publication Date, Geographical Scope, Legal and Sociological Focus. Literature that addresses the intersection of Islamic law, gender dynamics, and the sociological implications of marriage and divorce. Respondents from members of Muslim communities across diverse socio-cultural settings. This analysis is applied to identify variations in the application of Islamic family law in different regions. The findings reveal that local cultural norms and legal systems often influence Islamic principles governing marriage and divorce. While Islamic law emphasizes justice, mutual respect, and the protection of family welfare, its implementation varies significantly, creating diverse sociological outcomes. For example, in some regions, divorce laws have been adapted to address gender equality concerns, while in others, traditional practices continue to dominate, often to the detriment of women's rights. The study concludes that while Islamic family law provides a robust framework for regulating marriage and divorce, its sociological implications are shaped by the interplay between religion, culture, and modern legal reforms. To address the challenges faced by Muslim families, there is a need for a balanced approach that respects religious principles while promoting social justice and gender equality. This highlights the importance of ongoing dialogue and reform to ensure that Islamic family law remains relevant and supportive in modern societal contexts